Inoculation of Schizolobium parahyba with Mycorrhizal Fungi and Plant Growth-Promoting Rhizobacteria Increases Wood Yield under Field Conditions - Cely, Martha V. T.; Siviero, Marco A.; Emiliano, Janaina; Spago, Flávia R.; Freitas, Vanessa F.; Barazetti, André R.; Goya, Erika T.; Lamberti, Gustavo de Souza; dos Santos, Igor M. O.; De Oliveira, Admilton G.; Andrade, Galdino (Frontiers in Plant Science, 2016)
Schizolobium parahyba var. amazonicum (Huber ex Ducke) occurs naturally in the Brazilian Amazon. Currently, it is being planted extensively because of its fast growth and excellent use in forestry. Consequently, there is great interest in new strategies to increase wood production. The interaction between soil microorganisms and plants, specifically in the roots, provides essential nutrients for plant growth. These interactions can have growth-promoting effects. In this way, this study assessed the effect of the inoculation with arbuscular mycorrhizal fungi (AMF) and plant growth-promoting rhizobacteria (PGPR) on growth of S. parahyba var. amazonicum under field conditions. We used two native species of arbuscular mycorrhizal fungi, Claroideoglomus etunicatum (Ce), and Acaulospora sp. (Ac); two native strains of Rhizobium sp. (Rh1 and Rh2); and a non-native strain of Burkholderia sp. Different combinations of microorganisms were supplemented with chemical fertilizers (doses D1 and D2) in two planting methods, seed sowing and seedling planting. In seed sowing, the results showed that treatments with Ce/Rh1/Fertilizer D2 and Ac/No PGPR/Fertilizer D2 increased wood yield. In seedling planting, two combinations (Ac/Rh2/Fertilizer D1 and Ac/Rh1/Fertilizer D1) were more effective in increasing seedling growth. In these experiments, inoculation with AMF and PGPR increased wood yield by about 20% compared to the application of fertilizer alone.